Law, Society and Tax Law Enforcement in a Sharia Context - Fajrin Mubarokah Parhani; Dony Septriana Rosady; Titi Ratna Garnasih; Eka Juarsa; Siah Khosyi'ah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The paper